Analysis of the information ability of nurses in county hospitals in northern Henan province: a survey - Xizheng Li; Guirui Ma; Kuihong Qiao; Yuwen Yan; Huizhong Zhang; Yan Zhang (BMC, 2023)
Abstract Objective To investigate the status quo of nursing information ability of nurses in county-level hospitals and analyze its influencing factors. Methods In June 2022, a total of 303 on-the-job clinical nurses from 3 county-level hospitals in Hebi City, Henan Province were selected as subjects by convenience sampling method. General data questionnaire and self-rating nursing information ability scale were used to investigate them. Results The total score of nursing information ability of 303 nurses in county hospitals of Hebi City, Henan Province was (77.72 ± 18.76). There were statistically significant differences in the scores of nursing information ability among different ages, working years, positions, education, marriage, monthly income, whether they had learned computer-related knowledge and skills, and whether they had participated in the learning or training of nursing information system (all p < 0.05).Multiple linear regression analysis showed that age, years, position, monthly income and whether they had learned computer-related knowledge and skills were the main influencing factors of nursing information ability of county-level nurses (all p < 0.05). Conclusions The nursing information ability of nurses in county-level hospitals in northern Henan is at a medium level. The government or society should provide training and guidance on nursing information ability, so as to provide more opportunities for nurses in county-level hospitals to participate in and learn nursing information technology to improve their ability.